Effect of vitamin E on Semen Quality Parameters: A Meta-Analysis of a Randomized Controlled Trial - Wang, Rui; Wang, Shangren; Song, Yuxuan; Zhou, Hang; Pan, Yang; Liu, Li; Niu, Shuai; Liu, Xiaoqiang (Urology Journal, 2022)
Purpose: To explore the effectiveness of vitamin E in male infertility, a systematic review and meta-analysis was conducted. Materials and Methods: The retrieval time was from January 1947 to May 2021, without language restriction. Stata 12.0 was used for the meta-analysis. Results: A total of 8 randomized controlled trials involving 459 patients were included. The results showed that after vitamin E treatment, semen volume was reduced (95% CI: - 0.55 to - 0.06, SMD = - 0.30, p = 0.015), total sperm count was increased (95% CI: 0.02-0.45, SMD = 0.23, p = 0.035), and the differences were statistically significant. There were no statistically significant differences in increasing sperm concentration (95% CI: -0.21-0.29, SMD = 0.04, p = 0.769), total sperm motility (95% CI: -0.01-0.42, SMD = 0.20, p = 0.061) or sperm forward motility rate (95% CI: -0.06-0.65, SMD = 0.29, p = 0.106). Subgroup analysis showed that vitamin E treatment for six months could improve sperm forward motility (95% CI: 0.46-1.14, SMD = 0.80, p <0.001). Conclusion: Vitamin E could increase the total sperm count and reduce the volume of semen in male infertility patients, and long-term treatment could improve the forward motility rate of sperm. The decrease of semen volume may be the result of different abstinence time before and after the test.